The effects of using farm-pond algae as a liquid bio-fertilizer on spinach (Spinacia oleracea L.) growth (International Journal of Food and Nutritional Sciences, 2022)
By taking into consideration seed germination, seedling growth, and seedling vigour index, the effectiveness of farm pond algal extracts as a liquid bio-fertilizer on the growth of spinach was investigated (SVI). The experiment involved soaking the seed overnight in a variety of algal extract concentrations, including 1 per cent, 5 per cent, 10 per cent, 15 per cent, 20 per cent, 25 per cent, and control. The results showed that, when compared to other concentrations and the control, algal extracts at a 20 per cent concentration displayed the greatest activity in terms of increasing seed germination, root length, shoot length, and seedling vigour index.